2021
DOI: 10.1038/s41391-021-00345-0
|View full text |Cite
|
Sign up to set email alerts
|

Changes in body composition and lipid profile in prostate cancer patients without bone metastases given Degarelix treatment: the BLADE prospective cohort study

Abstract: Background Luteinizing hormone-releasing hormone (LHRH)-agonists in prostate cancer (PCa) patients induce sarcopenic obesity. The effect of LHRH-antagonist on body composition has never been explored. We evaluated changes in fat (FBM) and lean body mass (LBM) in PCa patients undergoing Degarelix. Methods This is a single-center prospective study, enrolling 29 non-metastatic PCa patients eligible to LHRH-antagonist from 2017 to 2019. All patients received monthly subcuta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 34 publications
3
11
0
Order By: Relevance
“…However, the effects of NAC only on body composition abnormalities and the prognostic impact of changes during NAC in patients with esophageal cancer remain unclear. It has been reported that androgen deprivation therapy, a prostate cancer treatment, causes body composition changes such as weight, fat gain, and muscle mass loss approximately 3-6 months after the start of treatment due to adverse effects [30,31]. These changes in body composition are known to cause sarcopenic obesity [32], which is associated with an increased risk of lipid disorders, insulin resistance, and cardiovascular events [33].…”
Section: Discussionmentioning
confidence: 99%
“…However, the effects of NAC only on body composition abnormalities and the prognostic impact of changes during NAC in patients with esophageal cancer remain unclear. It has been reported that androgen deprivation therapy, a prostate cancer treatment, causes body composition changes such as weight, fat gain, and muscle mass loss approximately 3-6 months after the start of treatment due to adverse effects [30,31]. These changes in body composition are known to cause sarcopenic obesity [32], which is associated with an increased risk of lipid disorders, insulin resistance, and cardiovascular events [33].…”
Section: Discussionmentioning
confidence: 99%
“…The limits of this study must be as well acknowledged. First, this represents only a preliminary analysis, as long-term data are awaited to define the impact of different treatment modalities and techniques on clinical outcomes and late toxicities [including, e.g., the metabolic effects of ADT ( 34 )].…”
Section: Discussionmentioning
confidence: 99%
“…Male patients with histologically confirmed PC without bone metastasis at bone scintigraphy, judged eligible to ADT according to current guidelines recommendations (Cornford et al 2017;Mottet et al 2017) after a multidisciplinary discussion, were enrolled. Eligibility criteria have been published elsewhere (Palumbo, et al 2021). Degarelix was administered as a subcutaneous injection with a starting dose of 240 mg, followed by a maintenance dose of 80 mg every 28 days.…”
Section: Trial Design and Endpointsmentioning
confidence: 99%
“…We recently conducted the BLADE study (Bone mineraL mAss Dexa dEgarelix), a prospective phase IV study designed to obtain explorative information on dual-energy x-ray absorptiometry (DXA) measurement changes in lean body mass (LBM) and fat body mass (FBM) in patients with non-metastatic PC treated with degarelix. Data on changes in total LBM and FBM and on the impact of degarelix on BMD and bone turnover markers were recently published (Palumbo et al 2021;Palumbo et al 2022).…”
Section: Introductionmentioning
confidence: 99%